PERSEPSI SISWA TERHADAP GURU BIMBINGAN KONSELING DI SMA NEGERI 1 SARUDU KECAMATAN SARUDU KABUPATEN PASANGKAYU PROVINSI SULAWESI BARAT - Asnia, Asnia; Adam, Adam; Latepo, Ibrahim (Program Studi Bimbingan dan Konseling Islam IAIN Palu, 2020)
The Objective of this research is to determine the role of counseling teachers at SMA Negeri 1 Sarudu. Techniques of data collections are data reduction, data presentation, and data verification (conclusion). The role of counseling teachers in SMA Negeri 1 Sarudu is used to educate and assist students in solving their problems through counseling at school. But the result showed that not all students had good perceptions of the counseling guidance by teachers. There were some of them assumed that counseling teacher at this school was less assertive in dealing with students who often skipped class.